Exploring Cadmium Sulfide as a Catalyst for the Solvent-Free Conversion of Benzyl Alcohol and 2-Phenoxy-1-Phenylethanol as Model Lignin Derivatives - Adiningtyas, Kusuma Virginna (Université d'Ottawa / University of Ottawa, 2024)
Concerns about fossil fuel depletion and environmental impact have led to exploring biomass as an energy source and feedstock for value-added chemicals. Lignin, a heterogeneous polymer and an abundant component of lignocellulosic biomass is a byproduct of the papermaking industry commonly burned as raw fuel. The underutilization of lignin stems from its highly aromatic structure and large size, making it challenging to break down and convert to more useful products. To that end, current research has focused on lignin valorization using various catalytic systems. Cadmium sulfide (CdS), a direct band gap semiconductor, is a promising catalyst due to its facile synthesis and favorable properties. The versatility of CdS nanoparticles (NPs) has been demonstrated in studies for applications such as carbon dioxide (CO₂) reduction, hydrogen evolution reactions (HERs) through water splitting, and the decomposition of organic molecules, which include lignin model molecules such as 2-phenoxy-1-phenylethanol (PP-ol). While photocatalytic and electrocatalytic activity of CdS is well-described, unlike other metal sulfides little is known about its thermocatalytic activity. This Thesis highlights the synthesis of CdS NPs of various crystalline phases and their characterization by X-ray diffraction (XRD), transmission electron microscopy (TEM), and Brunauer-Emmett-Teller (BET) surface area measurements. Ultraviolet and visible light (UV-vis) absorption and attenuated total reflection infrared (ATR-IR) spectra, as well as scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) measurements were also obtained for some select CdS NPs. The synthesized CdS NPs were used in a series of substrate conversion experiments, with benzyl alcohol and PP-ol as the probed model molecules. The resulting products of conversion were characterized by gas chromatography-mass spectrometry (GC-MS). Through experiments, the difference in catalyst morphology was found to affect photocatalytic activity in UV-assisted PP-ol conversion. In the series of solvent-free experiments employing select CdS NPs, we have demonstrated, for the first time, the catalytic activity of CdS NPs in the conversion of benzyl alcohol and PP-ol at high temperatures in the dark, and at mild temperatures under UV or visible light irradiation. More importantly, in the thermal reactions, we have showcased the formation of products through potentially distinct reaction pathways that were not observed under photocatalytic conditions, some of which have not been reported in literature. As the substrate conversions were successfully conducted under solvent-free and inert atmosphere conditions, we have demonstrated that these substrate conversions on CdS are solvent-independent and can take place without external gas. In other words, no air, oxygen (O₂), or hydrogen (H₂) atmosphere was necessary to drive the reactions. These conditions offer significant advantages in future heterogeneous catalysis applications. Where CdS contributions in thermal decomposition reactions have been overlooked, the preliminary results obtained and discussed in this Thesis help fill the existing knowledge gap on this subject and expand the potential use of CdS beyond typical photocatalytic and electrocatalytic applications.
Keywords: cadmium sulfide; lignin valorisation; heterogeneous catalysis; photocatalysis; solvent-free catalysis; benzyl alcohol; 2-phenoxy-1-phenylethanol